Interannual variability of the hydrology on the Sardinia shelf - Sorgente, Roberto; Pessini, Federica; Drago, Aldo Francis; Ribotti, Alberto; Genovese, Simona; Barra, Marco; Perilli, Angelo; Quattrocchi, Giovanni; Cucco, Andrea; Fontana, Ignazio; Giacalone, Giovanni; Basilone, Gualtiero; et al. (Frontiers in Marine Science, 2024)
The interannual variability of the physical properties of the shelf waters in Sardinia, western Mediterranean Sea, is studied by using hydrological data gathered during three oceanographic cruises: two in late summer of 2019 and 2021 respectively and another one in early autumn of 2020. The data consist of vertical profiles of salinity and potential temperature acquired by a multiparametric probe for a total of 171 casts performed along a set of transects extending from the nearshore to the continental slope, up to the depth of 200 m. Satellite remote sensing and numerical modelling oceanographic products support the phenomenological analysis. Atlantic Water, characterised by low salinity signatures (S<37.0), is detected in the surface waters of the southwestern shelf areas, induced by the Algerian Eddies, and with differences between years. It is also observed on the southern-eastern and north-eastern shelf areas of Sardinia, mainly driven by the interaction with large-scale circulation features like the southeast Sardinia Gyre and the Bonifacio Gyre. An upwelling phenomenology is identified as one of the major features of the coastal circulation on the western shelf area. The study provides the first assessment of the thermohaline features on the Sardinian shelf; an enhanced contribution to the current knowledge of the coastal sea phenomena, and contributes to numerical modelling applications and implementations for ecosystem services.